"Your Pants Won't Save You": Why Black Youth Challenge Race-Based Police Surveillance and the Demands of Black Respectability Politics. (January 2018) - Kerrison, Erin M.; Cobbina, Jennifer; Bender, Kimberly
The politics of "Black Respectability" foreground Black citizens' individual and collective responsibility to prioritize self-policing, polish, and propriety. Proponents believe that the steady performance of restraint and decorum is critical and that any departure from that repertoire can result in punishment. The belief that racially minoritized youth must earn respect and autonomy, rather than see those rights protected as a standard afforded to all community members, may not be widely held by younger Black people. The following study makes use of interview data collected from 23 Black Baltimore City millennials who shared their perspectives on the social and political contexts that led to Freddie Gray's death while in Baltimore Police custody. When discussing police officers' pursuit of citizens who match Freddie Gray's outward appearance, younger respondents resisted the demands of Black Respectability Politics and, instead, asserted their right to pass through their neighborhoods absent state-sanctioned harassment. This study features an exploration of how generational membership moderates legal socialization, attitudes about personal responsibility for police profiling, and beliefs about the right to the same full spectrum of freedoms and protections enjoyed by majority citizens. Implications for critical race theory, legal cynicism, and intergenerational coalition building are also discussed.